Avaliação do disseleneto de difenila e análogos como substratos da tioredoxina redutase - Freitas, Andressa Sausen de (2011)
Since the successful use of the organoselenium compound ebselen in clinical trials for the treatment of neuropathological conditions associated with oxidative stress, there have been concerted efforts geared towards understanding the precise mechanism of action of ebselen and other organoselenium compounds, especially the diorganyl diselenides such as diphenyl diselenide, and its analogs. Although the action mechanism of ebselen and other organoselenium compounds has been shown to be related to their ability to generally mimic native glutathione peroxidase (GPx), ebselen has also been shown to serve as a substrate for the mammalian thioredoxin reductase (TrxR), demonstrating another component of its pharmacological mechanisms, since thioredoxin reductase (TrxR) system plays important roles in cellular defense protecting against oxidative processes, possibly by the detoxification of hydroperoxides. In fact, there is a dearth of information on the ability of other organoselenium compounds, especially diphenyl diselenide and its analogs, to serve as substrates for the mammalian enzyme thioredoxin reductase. Therefore, in the present study, we tested the hypothesis that ebselen, diphenyl diselenide and some of its analogs (4,4 -bistrifluoromethyldiphenyl diselenide, 4,4 -bismethoxy-diphenyl diselenide, 4.4 -biscarboxydiphenyl diselenide, 4,4 -bischlorodiphenyl diselenide, 2,4,6,2 ,4 ,6 -hexamethyldiphenyl diselenide) could also be substrates for rat hepatic and cerebral TrxR. Then, Diphenyl diselenide, bismethoxydiphenyl diselenide and bischlorodiphenyl diselenide (at concentrations of 10, 15 and 20 μM) stimulated NADPH oxidation in the presence of partially purified brain and liver rat TrxR. However, Ebselen and bistrifluoromethyl-diphenyl diselenide that demonstrated to act as a substrate for liver TrxR did not serve as a substrate for cerebral TrxR. This fact can be explained by the differential expression of TrxR isoforms and the existence of alternative splice variants of TrxR in different mammalian tissues or cells. The results presented here, also, suggest that diphenyl diselenide displays neuroprotective properties by mimicking the activity of glutathione peroxidase and also act as a substrate for the enzyme thioredoxin reductase. However, Ebselen has not proven to be a good substrate for the brain TrxR, indicating that the neuroprotective property of this compound is due to its thiol peroxidase- like activity. Therefore, we show for the first time that diselenides are good substrates for mammalian TrxR, but not necessarily good mimetics of GPx, and vice versa. For instance, bis-methoxydiphenyl diselenide had no GPx activity, whereas it was a good substrate for reduction by TrxR. Our experimental observations indicate a possible dissociation between the two pathways for peroxide degradation (either via substrate for TrxR or as a mimic of GPx).